Creating institutional arrangements for managing water-scarce river basins: emerging research results - Merrey, Douglas J. (2000)
Because of increasing water scarcity in developing countries, poor people are suffering greatly from ?water deprivation.? One approach to improving water resources management is to develop river basin management institutions. This paper contrasts government-dominated approaches to forming such institutions with attempts to create stakeholder-based institutions. Two cases of the latter, in Mexico and South Africa, are compared to extract lessons for other countries.